Williams, John. Visions of the End in Medieval Spain. Catalogue of Illustrated Beatus Commentaries on the Apocalypse and Study of the Geneva Beatus. Ed. Therese Martin. Amsterdam: Amsterdam University Press, 2017. 291p - Miguélez Cavero, Alicia (2018)
SFRH/BPD/70305/2010